Strategi Bertahan Hidup Nelayan Di Desa Laguruda Kecamatan Sanrobone Kabupaten Takalar - Nirmala Nasir,; Abdul Malik,; Maddatuang, Maddatuang; Abdul Mannan,; Dinil Qaiyimah, (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study aims to determine the socio-economic conditions and what strategies are used to survive as fishermen in Laguruda Village, Sanrobone District, Takalar Regency. This study is a type of survey research while based on its analysis it is a qualitative descriptive study. Data collection techniques use observation, interview and documentation techniques. The variables in this study are social and economic aspects. The results of the study show that the social conditions are still relatively low levels of education, most are only elementary school graduates, then seen based on their economic conditions, the income level of fishermen is classified as moderate, ranging from Rp. 1,500,000 to 2,500,000 which has a figure of 43 percent. The strategies used by fishermen to survive are active strategies such as increasing working hours, looking for other jobs, and asking family members to work. Then passive strategies such as minimizing expenses, getting used to buying cheap goods and networking strategies that utilize social networks such as utilizing assistance from the government.